Plant Physiology, Development and Metabolism - Bhatla, Satish C; Lal, Manju A. (Springer, 2018)
Plants serve as a source for sustainable food and biofuel and also play crucial roles in maintaining human health and ecosystem. Thus, it becomes imperative to understand the mechanisms of plant growth and development. Plant physiology is that significant branch of plant science which deals with understanding the process of functioning of plants at cell, molecular, and whole plant levels and their interaction with the surrounding environment. In spite of being static in nature, plants can withstand adverse growth conditions due to a variety of adaptive mechanisms. Intracellular compartmentalization of biochemical pathways, expression of membrane-associated transporter proteins specific for various ions and metabolites, production of secondary metabolites with multiplicity of protective functions, and a wide variety of photoreceptors biochemically synchronized with various environmental and developmental conditions are some of the noteworthy adaptive features of plants enabling them to survive in almost all possible situations. The plethora of information available today has been made possible through interaction of cell and molecular biology, biochemistry, and genetics to understand plant processes. Plant physiology is an experimental science. Plant water relation is the first area of research in plant physiology which caught attention of scientists. Stephen Hales, also called as the Father of Plant Physiology, published the book Vegetable Staticks in 1727, highlighting various experimental studies on transpiration and root pressure. In the beginning of twentieth century, the development of physicochemical and biochemical techniques further facilitated the understanding of the plant processes. These techniques include spectral analysis, mass spectrometry, differential centrifugation, chromatography, electrophoresis, and the use of radioisotopes, besides many others. In the last two decades, plant physiologists made an extensive use of the molecular tools and Arabidopsis as a model organism to facilitate learning about the role of genes and the crosstalk among various biomolecules affecting plant functions and development. Lately, chemical biology has also contributed significantly through the use of small molecules to identify intracellular targets, thereby facilitating development of new herbicides and plant growth regulators. They are also used to identify novel signaling pathways. Small molecules are used to alter protein structure and explore the biological roles of target proteins (an area termed as chemical genetics). Low-molecular mass molecules are used as probes to modify biological processes. Major areas in plant physiology which have gained a lot of new information include growth and development (both vegetative and reproductive), physiology of nutrition, metabolism, and plant responses to the environment.